Particle size effects on yttrium aluminum garnet (YAG) phase formation by solid-state reaction. Issue 19 (14th October 2014) - Kupp, Elizabeth R.; Kochawattana, Sujarinee; Lee, Sang-Ho; Misture, Scott; Messing, Gary L.
Abstract: Abstract : The solid-state reaction of yttrium aluminum garnet (YAG, Y3 Al5 O12 ) during the heat treatment of Y2 O3 and Al2 O3 powder mixtures, differing in particle size and size ratio, was quantified using in situ high-temperature x-ray analysis and Rietveld refinement. Y2 O3 particle size has the most profound effect on YAG formation. When the Y2 O3 particle size was decreased from 5000 to 30 nm (on reaction with 270 nm Al2 O3 ), the YAG formation rate increased from 20 to 48 vol% min −1 over the temperature range of 1350–1450 °C. In this case, the final YAG content increased from 75 to 91 vol%. A simple model that includes the reactant particle coordination number, and thus particle size ratio, shows that when the size ratio ( d A / d Y ) is >1 diffusion through the alumina powder is rate controlling whereas when the ratio is <1, diffusion through the yttria, intermediate phases, and YAG is rate controlling.